Loss of Value Bundo Kanduang in the Attention of Parents Who Affect Stress in Young Stunting (Medico Legal Update, 2021)
Research goals to know the stress and stress risk factors of a parent’s attention to the loss of value BundoKanduang. Sampling techniques by purposive sampling. Data collection is conducted in the in-depthinterview, observation of participation, and secondary data. The Number of subjects 5 people. The researchwas conducted in March 2020. The subject of youth research stunting Padang. The attention of parents isthe dominant factor in causing stress. Based on the results of qualitative research of 5 informants. If parents’attention is good then low child stress levels For example children can control emotions, control themselves,be calmer when facing problems, easily socialize with the surrounding environment as well as vice versa.The loss of the value of Bundo Kanduang in the attention of parents greatly affects the stress experienced byteenagers. From qualitative analysis, 5 informants say the parents ‘ attention to risk factors related to stress.